Calcula x

3^{2x-1}-10\cdot3^{x}+27=0

 

 

 

 

 

 

0.04^{x}-0.2^{x+3}+0.2^{x}-0.016=0

 

 

 

 

 

 

0.5^{2x-1}-1.125\cdot0.5^{x}+0.0625=0

 

 

 

 

 

 

2^{x}+\frac{20}{2^{x}}=10.5

 

 

 

 

 

 

9^{x}-3^{x+2}+3^{x}-18=0

 

 

 

 

 

 

2^{x}+\frac{9}{2^{x}}=6.5

 

 

 

 

 

 

2^{2x-1}-5\cdot2^{x}+8=0

 

 

 

 

 

 

0.5^{2x}-2.625\cdot0.5^{x}+0.3125=0

 

 

 

 

 

 

2^{2x}-9.5\cdot2^{x}+12=0

 

 

 

 

 

 

0.2^{x}+\frac{0.06}{0.2^{x}}=1.54

 

 

 

 

 

 

0.25^{x}-0.5^{x+1}+0.5^{x}-1=0

 

 

 

 

 

 

5^{2x-1}-6\cdot5^{x}+25=0

 

 

 

 

 

 

0.5^{2x-1}-1.25\cdot0.5^{x}+0.125=0

 

 

 

 

 

 

0.04^{x}-0.2^{x+1}+0.2^{x}-0.8=0

 

 

 

 

 

 

25^{x}-5^{x+3}+5^{x}-375=0

 

 

 

 

 

 

0.5^{x}+\frac{0.375}{0.5^{x}}=3.125

 

 

 

 

 

 

0.5^{2x-1}-1.5\cdot0.5^{x}+0.25=0

 

 

 

 

 

 

2^{x}+\frac{18}{2^{x}}=8.5

 

 

 

 

 

 

0.2^{2x}-1.7\cdot0.2^{x}+0.3=0

 

 

 

 

 

 

0.2^{2x}-5.7\cdot0.2^{x}+1.1=0

 

 

 

 

 

 

5^{2x-1}-26\cdot5^{x}+125=0

 

 

 

 

 

 

5^{x}+\frac{75}{5^{x}}=28

 

 

 

 

 

 

10^{2x-1}-1001\cdot10^{x}+10000=0

 

 

 

 

 

 

4^{x}-2^{x+2}+2^{x}+8=0